TINJAUAN YURIDIS TERHADAP KLAIM ASURANSI KAPAL DI PT. ASURANSI ADIRA DINAMIKA - Fitriah, Ema (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT Emanation absence separation Ema Fitriah research titled  juridical review of insurance claims vessel in Pt .Insurance Adira Dinamika. Under the guidance of Dr.Abdul Munif,Sh.,M.Hum as one and Hj.Fatima Asyari,S.H., M.Hum as Tutors two  research aims to understand and analyze rights and obligations holder insurance policy in accordance with the provisions of legislative to know and analyze implementation and obstacles filing a claim insurance on a vessel Pt .Adira Dinamika       .The method used in this research was uses the method juridical empirical necessary to discuss the problems raised the review juridical against the claim of insurance on a vessel in Pt . Adira Dinamika of. In this research adopting nonjudicial case study, namely approach case study law without conflict. If conflict, settled by parties itself is peace, without the intervention of court. Of type this approach researchers conducted observation (observation directly on the process legal enactment on this particular occasion. Rights and obligations of the holder of the insurance policy is set in Kuhperdata, and then more specifically KUHD arranged at the consumer protection legislation. but the case in accordance with the results of empirical research that the compensation given to the insured has not been in accordance with the legislation. implementation of process claims the ship at Pt.Asuransi Adira Dinamika shall be in accordance with the provisions of the procedure that has been created in the treaty.External obstacles is obstacles which come from outside the power company, as inflicted by the community or to the insured own and others, internal obstacles was defined as obstacles which originates or also caused by companies are in the institution in itself Keywords: The institution The insured